PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI: KNOWLEDGE SHARING SEBAGAI MEDIASI - Saino, Rosita; Rajak, Adnan (Jurnal Manajemen Sinergi, 2021)
Objective: The purpose of this study is to know and analyze: (1) The influence of organizational culture positively and significantly on the Performance of Employees; (2) The positive and significant influence of organizational culture on knowledge sharing; (3) The effect of knowledge sharing positively and significantly on Employee Performance; and (4) The influence of organizational culture on Employee Performance through knowledge sharing at the Regional Office of the Ministry of Religion of the Province of North Maluku. The number of research samples were 92 employees.Methodology: The test instrument used was a structural equation model (SEM) using Partial Least Square (PLS) as a statistical test tool.Finding: Ha1, Ha2, and Ha3 are rejected, at the 5% confidence level.Conclusion: The results showed that: (1) Organizational culture had a positive and significant effect on employee performance at the Regional Office of the Ministry of Religion, North Maluku Province; (2) Organizational culture has a positive and significant effect on knowledge sharing at the Regional Office of the Ministry of Religion of the Province of North Maluku; (3) Knowledge sharing has a positive and significant effect on employee performance in the Regional Office of the Ministry of Religion of the Province of North Maluku; (4) Organizational culture has a positive and significant effect on employee performance through employee knowledge sharing at the Regional Office of the Ministry of Religion of the Province of North Maluku